(untitled) (Jurnal Manajemen dan Kewirausahaan, 2010)
The concept of entrepreneurship marketing is a scientific discipline that studies about the value, the ability and the person’s behavior in dealing with various problems related to business opportunities in an effort to get done. Through the concept of entrepreneurship marketing is by itself capable of creating a more focused business conditions related to attempt the achievement of those objectives. The purpose of this study is the first to know and analyze the variables include entrepreneurship marketing : concepts, strategies, methods and market intelligence simultanously influence sales performance. Second, to identify and analyze variables include entrepreneurial marketing concepts, strategies, methods and market intelligence influenced partially to the sales performance. Third, to identify and analyze variables include entrepreneurial marketing concepts, strategies, methods and market intelligence dominate the sales performance. Location of research on chips and small industries tempe in Malang. Type of research is explanatory research that analyzed the relationship the dependent variable and independent variables. Tool is a multiple linear regression analysis using SPSS for windows 16:00. To test the hypothesis by using F tests and t tests. From the analysis found that, first of entrepreneurial marketing variables that includes concepts, strategies, methods and market intelligence simultanously influence sales performance. Second, the variables include entrepreneurial marketing concepts, strategies, methods and market intelligence is partially an effect on the performance of the sale. Third, the strategy is entrepreneurial marketing variables that influence most of sales performance.